Birmingham and the (International) Business of Live Music in Times of COVID-19. (22nd June 2022) - Behr, Adam; Hamilton, Craig; Rozbicka, Patrycja
Abstract : This article discusses the context of, and presents findings from, a project examining the live music sector in Birmingham, UK. This research is set against the backdrop of the broader socio-political impact of the ongoing COVID-19 pandemic, and links it to national and global contexts. We explore the live music ecology of Birmingham and highlight the interdependencies between the various musical and non-musical stakeholders in the context of the pandemic—including the venues where live music takes place—examining how these stakeholders are responding to the crisis as it unfolds. In doing so, this article asks how an urban geographical area tied into national and international mechanisms of culture, commerce and policy can work to sustain its musical ecology in the face of the uncertainty of a post-COVID-19 era, and underlines the interconnectedness of live music ecologies and wider economies.